Dereplication of phenolic derivatives of qualea grandiflora and qualea cordata (vochysiaceae) using liquid chromatography coupled with ESI-QToF-MS/MS - Neto, Fausto Carnevale [UNESP]; Siquitelli, Cristian D. [UNESP]; Pilon, Alan C. [UNESP]; Silva, Dulce H.S. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Castro-Gamboa, Ian [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2013)
A rational and selective method using on-line high-performance liquid chromatography (HPLC) coupled with electrospray quadrupole time-of-flight tandem mass spectrometry (ESI-QToF-MS/MS) was established for the dereplication of phenolic derivatives from Qualea grandiflora and Qualea cordata. The selection of the extracts was based on the antioxidant capacity measured by in vitro DPPH assay. The HPLC-ESI-QToF-MS/MS analysis was conducted by on-flow detection, using high-resolution mass/ratio ions as well as collision induced MS/MS experiments for selected protonated ions. The dereplication of the EtOAc fraction from the hydro alcohol extract from the stem bark of Q. grandiflora allowed the detection of the flavonoids: 3',4',5',5,6,7-hexahydroxy- 8 methylflavanone, 8-methyl-naringenine and 3',7-dimethoxy-8 methyl-4',5,7- trihydroxyflavanone, as well as a benzophenone derivatives: bis(4,6-dimethoxy-2- hydroxy-3-methylphenyl)- metanone, 3',4'-dimethoxy-8-methyl-5,6,7 trihydroxyflavanone, 7-methoxy-6-methyl- 3',4',5 trihydroxyflavanone, 6,8-dimethyl-3' methoxy-4',5,7 trihydroxyflavanone and 3',5'-dimethoxy-6,8- dimethyl-4',5,7 trihydroxyflavanone were detected in the EtOAc fraction from the hydro-alcohol extract from the leaves of Q. cordata. © 2013 Sociedade Brasileira de Química.
Keywords: Dereplication; HPLC-ESI-QToF-MS/MS; Qualea cordata; Qualea grandiflora; Radical scavenging activity